(untitled) (Kriminalističke teme, 2008)
This study uses self-report data from a purposive sample of 2206 youth in Bosnia and Herzegovina (BiH) ages 13 to 17 to examine the prevalence and correlates of minor offending, serious offending, and substance use. Principles from public health prevention science are presented to provide a framework for the study as part of a comprehensive strategy against offending in BiH. Descriptive results indicate the prevalence of offending and substance use is relatively low in BiH and comparable to prevalence in the US and Germany, although interesting differences exist across countries. Results of multivariate analyses reveal that male gender and age are strongly associated with higher levels of offending and substance use. Differences in prevalence rates by city are also statistically significant, with youth from Sarajevo reporting more minor and serious offending, and youth from Banja Luka and Mostar reporting more substance use. A prevention framework guides interpretation of results, focusing on a need to target scarce resources more precisely.